Kenisha : the roots and development of the evangelical church of Eritrea 1866-1935 - Lundstrom, Karl Johan, 1927-2003.; Gebremedhin, Ezra. (New Jersey: : The Red Sea press, 2011)
Icncludes bibliographical reference and index.
Keywords: Evangelical church of Eritrea -- history; Eritrea -- church history